Oral-Gut Microbiome Analysis in Patients With Metabolic-Associated Fatty Liver Disease Having Different Tongue Image Feature - Lu, Chenxia; Zhu, Hui; Zhao, Dan; Zhang, Jia; Yang, Kai; Lv, Yi; Peng, Miao; Xu, Xi; Huang, Jingjing; Shao, Zuoyu; Xiao, Mingzhong; Li, Xiaodong (Frontiers in Cellular and Infection Microbiology, 2022)
Objective: To identify the biological correlation between the tongue coating color and oral and gut micro-characteristics of metabolic-associated fatty liver disease (MAFLD) patients in oral and gut . Method: The characteristic parameters of the tongue coating were extracted using an automatic tongue diagnosis system. Tongue coating and stools samples were collected from 38 MAFLD patients, and the 16S rDNA full-length assembly sequencing technology (16S-FAST) was used for bioinformatic analysis. Results: 22 and 16 subjects were defined as two distinct clusters according to the white/yellow color of coating on the tongue，which showed depth of thermal property assessed by L*a*b* values of tongue coating image.Upon analyzing the microorganisms in tongue coating, 66 and 62 pathognomonic bacterial genera were found in White Coating Group and Yellow Coating Group,respectively.The abundance of Stomatobaculumis positively correlated with the a*values of the tongue coating in White Coating Group, while Fusobacterium, Leptotrichia, and Tannerella abundance significantly correlated with the b*values in Yellow Coating Group. Function prediction mainly involves protein families processes of Brite Hierarchies and Metabolism. Conclusion: In MAFLD patients, there are significant differences between yellow and white tongue coating in accordance with L*a*b* values of optical image analysis . Significantly,the lower a*values, the higher b*values are optically closer to yellow tongue coating,and indicating a correlation between carbohydrate metabolism disorders and inflammation in the oral microbiome.